A THEORETICAL FRAMEWORK: FINANCIAL PERFORMANCE OF COMPANIES USING THE BALANCED SCORECARD - Dias, Ibsem Agrello (2014)
This paper aims to conduct a literature survey from a structured process, proposed by Gerber et al. (2013), through the selection of scientific articles on the issue of improving the financial performance of organizations which have adopted the Balanced Scorecard. The key research question is to evaluate the perception of improved financial performance. As a result, four articles aligned to the research topic were obtained. Systemic analysis highlights the existence of gaps on the subject that offer the proposition of new research studies designed to evaluate the contribution of the BSC to the financial performance of organizations.